Gut Microbiota: A Promising Milestone in Enhancing the Efficacy of PD1/PD-L1 Blockade Therapy - Zhou, Yuqing; Liu, Zhaoxia; Chen, Tingtao (Frontiers in Oncology, 2022)
In the past few decades, immunotherapy has emerged as one of the most promising strategies among current treatments of cancer. In particular, the field of PD1/PD-L1 inhibitors has been boosted, widely applied into clinical practice with potent therapeutic efficacy and remarkable survival benefits on various cancers such as melanoma, non-small cell lung cancer (NSCLC), and urothelial carcinoma (UC). However, the application of PD1/PD-L1 blockade therapy is still quite restricted because of unexpected toxicities, limited response rate, as well as associated resistance. In consequence, searching for potential strategies that possibly resolve the existing limitations and enhance the therapeutic responsiveness of PD1/PD-L1 blockade is of great significance. Fortunately, the gut microbiome has been demonstrated to serve as a pivotal regulator in anti-PD1/PD-L1 therapy, providing an applicable tool to improve anti-PD1/PD-L1 clinical efficacy. In this review, we summarized published advancements about how microbiota modulated in anti-PD1/PD-L1 therapy and illustrated its underlying mechanisms, giving insights into putative manipulation of gut microbiota to facilitate PD1/PD-L1 blockade.